Dynamic and non‐neutral productivity effects of foreign ownership: A nonparametric approach. (18th November 2022) - Lee, Yoonseok; Lovely, Mary E.; Pham, Hoang
Summary: This paper studies two novel productivity characteristics of foreign acquisition on high‐tech manufacturing firms: the dynamic and the non‐Hicks‐neutral effects. A dynamic productivity effect of foreign ownership arises when adoption of foreign technology and management practices takes time to fully realize. Furthermore, these dynamic adjustments may be capital or labor augmenting as adoption of advanced production technologies tends to have non‐neutral productivity implications in developed countries. We propose and implement an econometric framework to estimate both effects using firm‐level data from China's manufacturing sector. Our framework extends a nonparametric productivity framework, in which identification is achieved using a firm's first‐order conditions and timing assumptions. We find strong evidence of dynamic and non‐neutral effects from foreign ownership, with significant differences across investment sources. Investment from OECD sources is found to provide a long‐term productivity boost for all but the largest recipients, while that from Hong Kong, Macau, and Taiwan does not raise performance. These findings have implications for China's declining labor share and for the rising domestic value‐added content of its high‐tech exports.